For a new generation of mafia and anti-mafia scholars (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The editorial gives an overview of the new issue beginning with a reflection on the newly formed Italian Society of Mafia and Anti-Mafia Scholars, then continuing with a description of the other contributions.